Predictors of financial well-being and mediating effect of financial behaviour among public employees in Putrajaya, Malaysia - Mokhtar, Nuradibah (2016)
Generally, finance has been comprehended as an individual’s future cash flows which require a proper money management. Hence, financial management amongst individual could affect dissatisfaction or satisfaction of an individual’s financial situation which known as financial well-being. Financial characteristics is determined by, and therefore an indicator of the financial well-being. The main objective of this study was to examine the factors related to financial well-being among public employees. The family resource management theory, family stress management theory and ABCD-XYZ Resource Management Model of Crisis/Stress functioned as the basis for the theoretical framework of the study. A conceptual framework was established from the theoretical settings to identify the financial characteristics influences of demand related factors (financial stress,rewards and promotions, facility and safety and interrelationships), resource related factors (internal locus and external locus of control) and financial behaviour on financial well-being. The study also investigated the mediating effects of financial behaviour in the relationships between financial characteristics and financial well-being. A multistage random sampling was used to gather the 500 data public employees from four ministries, namely, Ministry of Human Resource,Ministry of Domestic Trade, Co-Operatives and Consumerism, Ministry of Education and Ministry of Youth and Sport located in the Federal Territory of Putrajaya. The self-administered questionnaire was disseminated using online survey technique. There were 374 useable and completed questionnaire maintained for the analysis of the study. The data were statistically analyzed using descriptive analysis and Structural Equation Modelling via Smart PLS. A relatively good fit of the model (R2 = 0.495) to the data was obtained in the study. There were significant linear relationships found between financial stress (β = -0.542, p= 0.000), financial behaviour (β = 0.266, p = 0.000) and external locus of control(β = 0.085, p = 0.039) towards financial well-being. The financial behaviour was distinguished as a mediator in the relationships between external locus of control and financial well-being. This study seemed to support the importance of financial characteristics, with the empirically substantiated findings alongside the theoretical rationalizations, in understanding the financial well-being of public employees. This study provides a predictive framework explaining financial wellbeing of the public employees. The present study suggests that the interventions have to be addressed at multiple targets within system levels in behalf of the relationships of different individuals attached into these systems. Predictably,interventions that focus on a micro level will be insufficient to deal with acquire of financial well-being. Therefore, it is suggested to integrate all financial well-being predictors to address multiple related issues and implement research knowledge as well as good practices while formulating interventions.